Tinjauan Pengisian Formulir Informed Consent Pasien Dengan Tindakan Hecting di Puskesmas X Kabupaten Tasikmalaya - Gunawan, Reza Maulana; Sugiarti, Ida (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
Approval for medical action or Informed Consent is required to ensure that the patient has understood all the information provided to make a decision and the patient gives consent or refusal. Informed consent is useful as legal evidence to reduce the risk of problems or claims against doctors or health care facilities for actions taken on patients. So the completeness of filling out the informed consent form is very important in community health centers. The X Health Center, Tasikmalaya Regency, has not fully complied with the completeness of filling out the informed consent form.Knowing the completeness of filling out the Informed Consent Form for Patients with Hectating Actions at the X Community Health Center, Tasikmalaya Regency. The research method used was a quantitative descriptive design with a sample of 44 Informed Consent patients with Hecting procedures based on the total sampling of patient visits in the 2023 treatment room. The results of the research on the completeness of filling out informed consent in the Patient Identification review were 78% complete, the Important Report review was 67% complete, the Authentication review was 63% complete, the Good Documentation review was 81.2% complete and from the four components of the recording review the results were 69% complete and 31% incomplete. The completeness of filling out informed consent has an important role in supporting the quality of service aspects as well as the legal aspects of the form as legal evidence for patients and health service facilities.